2021
DOI: 10.2106/jbjs.rvw.21.00065
|View full text |Cite
|
Sign up to set email alerts
|

Is Frailty Associated with Adverse Outcomes After Orthopaedic Surgery?

Abstract: Background:There is increasing evidence supporting the association between frailty and adverse outcomes after surgery. There is, however, no consensus on how frailty should be assessed and used to inform treatment. In this review, we aimed to synthesize the current literature on the use of frailty as a predictor of adverse outcomes following orthopaedic surgery by (1) identifying the frailty instruments used and (2) evaluating the strength of the association between frailty and adverse outcomes after orthopaed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 124 publications
0
49
0
Order By: Relevance
“…However, the extent to which frailty impacts perioperative surgical and acute medical complications in TJA has been explored in relatively few large-scale studies [ 18 20 ]. In the review of Lemos et al, it was pointed out that some studies have shown that preoperatively frail patients were closely related to perioperative complications and mortality after joint replacement [ 21 ]. However, the sample size in the existing studies is far smaler than the sample size of this experiment [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the extent to which frailty impacts perioperative surgical and acute medical complications in TJA has been explored in relatively few large-scale studies [ 18 20 ]. In the review of Lemos et al, it was pointed out that some studies have shown that preoperatively frail patients were closely related to perioperative complications and mortality after joint replacement [ 21 ]. However, the sample size in the existing studies is far smaler than the sample size of this experiment [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…14 Therefore, our findings suggestthatpatientswaitingmorethansixmonthsforsurgery willbemorefrailandbeatanincreasedriskofperioperative complicationsandmortality. 14 Thiswillalsohavecostimplications for healthcare systems managing the complications andlongerlengthofstayinhospital. 14,44 The independent factors associated with deterioration in HRQoLandincreasingfrailtycouldbeusedtoidentifypatients whoareatrisk,andinterventionscouldbeofferedwhilethey await surgery.…”
Section: Discussionmentioning
confidence: 73%
“…Deterioration in HRQoL leads to an increased morbidity and progressive frailty, and increasing frailty is associated with increased mortality,lengthofstayinhospital,andtherateofreadmission. [13][14][15] Thus, patients awaiting THA and KA may have a greatly increased risk of perioperative complications and longerlengthsofstay. 16 PatientsatriskofworseningHRQoL or increasing frailty while waiting for surgery may benefit fromfocusedpreoperativemanagementtooptimizethemfor surgery and prevent their deterioration.…”
mentioning
confidence: 99%
“…In regard to hip fractures, frail patients with dementia have been found to be less likely to receive in-hospital rehabilitation, while frail patients that do receive rehabilitation often experience poorer outcomes [ 51 , 52 ]. Frailty has also been observed to be associated with increased mortality, morbidity, as well as a reduced quality of life after hip fracture surgery [ 53 55 ]. Moreover, frail patients are at an increased risk of developing dementia, which may partially explain the high prevalence of dementia among hip fracture patients [ 9 , 29 , 56 ].…”
Section: Discussionmentioning
confidence: 99%